2020
DOI: 10.3892/ol.2020.11840
|View full text |Cite
|
Sign up to set email alerts
|

Ring box protein-1 is associated with a poor prognosis and tumor progression in esophageal cancer

Abstract: Ring box protein-1 (RBX1) is an essential component of the S-phase kinase-associated protein, Cullin and F-box containing ubiquitin ligases. Overexpression of RBX1 has been reported in several cancer types; however, little is known regarding the prognostic value and role of RBX1 in esophageal cancer. The present study examined 120 patients with esophageal cancer (EC) who underwent curative esophagectomy and 61 patients with EC who underwent neoadjuvant combination chemotherapy with docetaxel, cisplatin and 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…RBX1, also called ROC1, is a major component of E3 ubiquitin ligase [ 8 , 9 ]. It has evolved from yeast to humans and has exerted a major effect in the development of embryos [ 9 , 15 ]. Recent researches have exhibited that RBX1 not only exerts a critical role in modulating several cellular physiological functions, but is also participated in the cancer development [ 8 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…RBX1, also called ROC1, is a major component of E3 ubiquitin ligase [ 8 , 9 ]. It has evolved from yeast to humans and has exerted a major effect in the development of embryos [ 9 , 15 ]. Recent researches have exhibited that RBX1 not only exerts a critical role in modulating several cellular physiological functions, but is also participated in the cancer development [ 8 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 , 13 ] Kunishige et al have concluded that downregulation of ROC1 significantly disrupt the proliferation of esophageal cancer cells through regulation of p21. [ 6 ] Celik et al have demonstrated that overexpression of ROC1 is associated with advanced clinical stage and high prostate specific antigen (PSA) levels in prostate cancer patients and depletion of ROC1 crucially induces apoptosis, senescence, autophagy and G2/M arrest in prostate cancer cells. [ 12 ] Several studies have indicated that overexpression of ROC1 is connected with higher Fuhrman grade and ROC1silencing remarkably hinders cancer cells growth and survival through G2/M arrest, senescence and apoptosis by accumulation of WEE1, p21, p27, NOXA, and BIM in renal cell carcinoma (RCC).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, increased ROC1 expression is associated with large tumor size, lymph node metastasis (LNM) and Tumor Node Metastasis (TNM) stage in a diversity of neoplasms. [6,8,10,[12][13][14][15] So elevated expression of ROC1 could be a potential biomarker for identifying patients with poor prognostic factors and advanced clinical features, serving as a potential target for cancer therapy. [9,11,16] Due to the limited sample size in present studies, we carried out this meta-analysis to elucidate the association of ROC1 between the prognosis and clinicopathologic characteristics in cancer patients, thus estimating the potential value of ROC1 as a promising prognostic predictor in human tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the phenotypic consequences corresponding with cancer development (e.g., CIN) following aberrant expression of SCF complex members may vary and are likely to arise via the misregulation of protein substrates in a contextdependent manner. For example, overexpression of SCF complex members may result in excess degradation of protein substrates with tumor suppressor functions, and has been associated with cancer cell stemness, tumor progression and worse patient survival [79][80][81][82][83][84][85][86].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the phenotypic consequences corresponding with cancer development (e.g., CIN) following aberrant expression of SCF complex members may vary and are likely to arise via the misregulation of protein substrates in a context-dependent manner. For example, overexpression of SCF complex members may result in excess degradation of protein substrates with tumor suppressor functions, and has been associated with cancer cell stemness, tumor progression and worse patient survival [ 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ]. Similarly, amplification and overexpression of SKP2 promotes the increased degradation of P27 and disease progression [ 56 ] and is associated with worse survival outcomes and poor response to therapy in numerous cancer types [ 87 , 88 , 89 ], contributing to SKP2 being traditionally classified as an oncogene.…”
Section: Discussionmentioning
confidence: 99%